Edukasi Interaktif tentang Bahaya Rokok pada Siswa SMP Negeri 4 Limboto - Mahdang, Putri Ayuningtias; Maksum, Tri Septian; Arsad, Nikmatisni; Sunardi, Sunardi (Universitas Negeri Gorontalo, 2025)
Smoking behavior is a common phenomenon in Indonesian society. For the majority of Indonesians, smoking is a behavioral pattern that occurs in daily life. Smoking habits among adolescents in Indonesia are quite frequent, as this age represents a transitional period from adolescence to adulthood. The development of smoking behavior in adolescents is influenced by the knowledge they possess. Knowledge serves as the most fundamental basis for shaping a person's actions; it is the result of sensory perception or awareness of an object through their senses. The community service activity was conducted at SMP Negeri 4 Limboto with a total of 39 participants, consisting of 7th and 8th grade students. The activity was carried out in May 2025. The method used involved providing interactive education to the students. The activity was implemented in three stages: planning, preparation, implementation, and evaluation. Most of the students already possessed a very good level of knowledge and were aware of the health risks associated with smoking. However, smoking practices among students still occur, mainly due to peer pressure, lack of supervision, and easy access to cigarettes. Through collaboration among all parties, it is hoped that smoking behavior among students can be minimized and a culture of healthy living can be fostered within the educational environment.Keywords:Adolescents, Education, Knowledge, Smoking behavior